Teaching as leadership : the highly effective teacher's guide to closing the achievement gap - Farr, Steven. 4 0 16; 5 (San Francisco : Jossey-Bass, 2010)
Outlines key strategies that teachers can use to boost student achievement in the classroom, focusing on how teachers in poor communities can help their students overcome challenges and succeed in school.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Effective teaching.;School improvement programs.;Academic achievement.;Educational leadership.;Teaching.; 20; 2